Analysis of Information System Security in the Context of Cyber Attacks on Business Organizations - Marliana, Iin; Eko Hendro Pramono, Doni; Yuniarthe, Yodhi; Dwi Yunita, Hilda; Zuhri, Khozainuz (RISTEC : Research in Information Systems and Technology, 2024)
Cyberattacks have become a significant threat to business organizations in the digital era. This study aims to analyze the security of information systems in mitigating cyber threats targeting businesses. The research employs a systematic literature review method to explore various cyberattack techniques, identify vulnerabilities in information systems, and propose effective prevention and mitigation strategies. Findings indicate that cyberattacks are increasingly sophisticated, necessitating adaptive and multi-layered security approaches to safeguard information systems. The study concludes that proactive measures, including robust authentication, encryption, and user training, are essential for enhancing cybersecurity resilience in business organizations.